PERLINDUNGAN HAK ASASI MANUSIA DALAM KONSTITUSI INDONESIA - Thaher, Irmanjaya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Human rights are a fundamental pillar of modern legal and constitutional architecture, guaranteeing the dignity, freedom, and equality of individuals. Indonesia, as a democratic state governed by the rule of law, has a constitutional obligation to protect human rights, as stated in the 1945 Constitution.This study analyzes the human rights protection system in the Indonesian constitution through four dimensions: the constitutional guarantees of the post-amendment 1945 Constitution, the institutional roles of the Constitutional Court and the National Commission on Human Rights (Komnas HAM), gaps between norms and implementation, and the protection of minority rights and the principle of non-discrimination.The research methodology employed a Systematic Literature Review (SLR), conducted systematically, transparently, and structured to identify, evaluate, and synthesize relevant scholarly articles to obtain a comprehensive, evidence-based understanding.The results show that the post-amendment 1945 Constitution provides comprehensive constitutional guarantees for human rights, but significant gaps remain in implementation. The Constitutional Court and Komnas HAM play strategic roles but face limited authority and political support. Implementation barriers are multidimensional, encompassing socio-political factors, weak legal mechanisms, and structural institutional weaknesses.The study concluded that human rights protection in Indonesia requires strengthening public legal literacy, consistent enforcement of constitutional norms, increased institutional capacity, and comprehensive reform. Protection of minority rights based on Article 28I Paragraph (4) of the 1945 Constitution is still not optimal due to weak law enforcement and discriminatory regional regulations, so that synchronization of national-regional regulations is an urgent agenda.